The Role of Midwives in Increasing Participation in IUD Family Planning at the Bone Pantai Community Health Center - Meta Aquarista Syamsi; Sulistiyah Sulistiyah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Background: Family planning is a critical public health strategy to control population growth and improve maternal and child health. Among the available contraceptive methods, the Intrauterine Device (IUD) is highly effective and long-term, yet its uptake remains low in many communities. Midwives play a pivotal role in promoting IUD adoption through counselling, education, and community engagement, but their effectiveness in specific local contexts requires further investigation. Objective: This study aimed to examine the role of midwives in increasing women’s participation in IUD family planning at the Bone Pantai Community Health Center. Methods: A quantitative descriptive-analytical study with a cross-sectional design was conducted. The population included women of reproductive age (15–49 years) eligible for IUD contraception and midwives providing family planning services. A purposive sampling technique was used to select participants. Data were collected through structured questionnaires, interviews, and observation checklists. Statistical analysis was performed using SPSS software, with descriptive statistics to summarize participant characteristics and inferential tests, including the Chi-square test, to examine relationships between midwife interventions and IUD uptake.